Evaluation of new treatments for benign prostatic obstruction: ICI-RS 2023 - TARCAN, TUFAN (My University, 2023)
Aims: To address how invasive therapies for benign prostatic obstruction (BPO) have been evaluated, what their effect is on BPO, if they can prevent progression to BPO and how new therapies need to be evaluated before implementation into clinical practice. Methods: The think tank conducted a literature review and looked at the previous and current American Urological Association, European Association of Urology and the International Consultation on Urological Diseases guidelines to see what procedures have been used to treat BPO. They then assessed whether trials have been conducted before implementation of the procedures and whether they have been compared to a “gold” standard treatment. The use of urodynamics has also been addressed in the think tank in relation the clinical trials as well as terminology. Results: Guidelines vary in the use of terminology when it comes to BPO with some continuing to use the term benign prostatic hyperplasia (BPH). There are several procedures for example, TUNA, which have become obsolete although continues to be mentioned in the guidelines until recently. Majority of procedures have been introduced without comparing to “gold” standard treatment and without any long‐term data. There continues to be many unknowns with regard to the success of some of the BPO procedures and why some of the adverse events develop. Conclusion: There needs to be more robust long‐term clinical trials conducted of new BPO therapies, with men who have both lower urinary tract symptoms and urinary retention, before introduction into clinical practice.
Keywords: benign prostatic hyperplasia; benign prostatic obstruction; HoLEP; TURP; urodynamics